PERAN HABIT SEBAGAI MEDIATOR PENGARUH KESIAPAN TEKNOLOGI TERHADAP NIAT ADOPSI AI MAHASISWA - Saputri, Ulfah Tika; Febrianti, Devi; Firza, Edy; Zulkifli; Rohimah, Sania Isti; Nurhalizah; Putra, M. Dwi (Jurnal Riset Terapan Akuntansi, 2025)
This study aims to analyze the effect of Technology Readiness (TR) on Intention to Adopt (IA) in completing complex assignments among vocational accounting students, with Habit as a mediating variable. This research employed a quantitative survey method with 500 accounting students from vocational higher education institutions in Palembang City as respondents. The data were analyzed using PLS-SEM. The results show that TR has a positive and significant effect on IA, and Habit also has a positive and significant effect on IA. In addition, Habit is proven to mediate the relationship between TR and IA. These findings highlight that technology readiness and habitual use of technology play an important role in supporting students’ intentions to adopt AI-based technology as a tool for completing complex assignments in the vocational education context. Keywords: Technology Readiness; Habit; and Intention to Adopt.